Taking sides clashing views on controversial issues in drugs and society - Goldberg, Raymond (Guilford, Connecticut McGraw-Hill/Dushkin, 2002)
Is a debate-style reader designed to introduce students to controversies in drug use and misuse in contemporary society. The reading, which present the arguments of leading social scientists, health care professionals, and social commentators, reflect a variety of viewpoints and have been selected for their liveliness and substance and because of their value in debate framework. For each issue, the editor provides a concise introduction and postscript summary. The introduction sets the stage for the debates as it is argued in the "yes" and "no" readings, and the postscript briefly reviews the opposing views and suggests additional readings on the controversial issue under discussion.--Cover.
Part 1. Drugs and public policy -- Should drug be legalized? -- Should the United States put more emphasis on stopping the importation of drugs? -- Should congress impose a lower blood alcohol concentration limit for drunk driving? -- Should needle exchange programs be supported? -- Should pregnant drug users be prosecuted? -- Should young people be taught how to use marijuana? -- Is harm reduction a desirable national drug control policy goal? -- Should tobacco products be more closely regulated? -- Part 2. Drugs and social policy -- Should marijuana be legal for medicinal purposes? -- Should doctors promote alcohol for their patients? -- is nicotine addictive? -- Are too many children receiving Ritalin? -- Is Prozac over prescribed? -- Part 3. Drug prevention and treatment -- Should the food and drug administration prohibit tobacco advertising? -- is total abstinence the only choice for alcoholics? -- Is drug abuse resistance education (DARE) an effective program? -- Should the decision to use anabolic steroids be left to athletes? -- Does drug abuse treatment work? -- Are anti drug media campaigns effective?
Includes bibliographical referenced and index.
Keywords: Drug abuse -- Prevention; Drug abuse -- Treatment; Drug abuse -- Social aspects -- United States